ÉPICO: Proceso de creación en pandemia sobre el teatro épico de Brecht (Urdimento: Revista de Estudos em Artes Cênicas, 2021)
This article aims to socialize the modes of production of the research and creation process of ÉPICO, by Tercer Abstracto company (Chile/Brazil), in order to answer the questions: How to work the political and artistic proposals of Bertolt Brecht in times of pandemic? How to elaborate, from the epic theater, a scenic experiment designed for the virtual environment? From the analysis of documents, the elaborations of explicit thought by Tercer Abstracto and the final result of the piece ÉPICO, it is intended to demonstrate how the pandemic and tecnoviviality affected the research process, leading it to an experimentation in the virtual environment about the working conditions and collective organization in pandemic times.
Keywords: Bertolt Brecht; Epic Theater; Tercer Abstracto; Research and Creation Methodologies; Pandemic